Distribution of avian influenza viruses according to environmental surveillance during 2014-2018, China - Hong Bo; Ye Zhang; Li-Bo Dong; Jie Dong; Xi-Yan Li; Xiang Zhao; Zi Li; Yue-Long Shu; Da-Yan Wang (BMC, 2021)
Abstract Background Recurrent infections of animal hosts with avian influenza viruses (AIVs) have posted a persistent threat. It is very important to understand the avian influenza virus distribution and characteristics in environment associated with poultry and wild bird. The aim of this study was to analyze the geographic and seasonal distributions of AIVs in the 31 provinces, municipalities and autonomous region (PMA) of China, compare the AIVs prevalence in different collecting sites and sampling types, analyze the diversity of AIVs subtypes in environment. Methods A total of 742 005 environmental samples were collected from environmental samples related to poultry and wild birds in different locations in the mainland of China during 2014-2018. Viral RNA was extracted from the environmental samples. Real-time RT-PCR assays for influenza A, H5, H7 and H9 subtypes were performed on all the samples to identify subtypes of influenza virus. The nucleic acid of influenza A-positive samples were inoculated into embryonated chicken eggs for virus isolation. Whole-genome sequencing was then performed on Illumina platform. SPSS software was used to paired t test for the statistical analysis. ArcGIS was used for drawing map. Graphpad Prism was used to make graph. Results The nucleic acid positivity rate of influenza A, H5, H7 and H9 subtypes displayed the different characteristics of geographic distribution. The nucleic acid positivity rates of influenza A were particularly high (25.96%-45.51%) in eleven provinces covered the Central, Eastern, Southern, Southwest and Northwest of China. The nucleic acid positivity rates of H5 were significantly high (11.42%-13.79%) in two provinces and one municipality covered the Southwest and Central of China. The nucleic acid positivity rates of H7 were up to 4% in five provinces covered the Eastern and Central of China. The nucleic acid positivity rates of H9 were higher (13.07%-2.07%) in eleven PMA covered the Southern, Eastern, Central, Southwest and Northwest of China. The nucleic acid positivity rate of influenza A, H5, H7 and H9 showed the same seasonality. The highest nucleic acid positivity rates of influenza A, H5, H7, H9 subtypes were detected in December and January and lowest from May to September. Significant higher nucleic acid positivity rate of influenza A, H5, H7 and H9 were detected in samples collected from live poultry markets (LPM) (30.42%, 5.59%, 4.26%, 17.78%) and poultry slaughterhouses (22.96%, 4.2%, 2.08%, 12.63%). Environmental samples that were collected from sewage and chopping boards had significantly higher nucleic acid positivity rates for influenza A (36.58% and 33.1%), H5 (10.22% and 7.29%), H7(4.24% and 5.69%)and H9(21.62% and 18.75%). Multiple subtypes of AIVs including nine hemagglutinin (HA) and seven neuraminidase (NA) subtypes were isolated form the environmental samples. The H5, H7, and H9 subtypes accounted for the majority of AIVs in environment. Conclusions In this study, we found the avian influenza viruses characteristics of geographic distribution, seasonality, location, samples types, proved that multiple subtypes of AIVs continuously coexisted in the environment associated with poultry and wild bird, highlighted the need for environmental surveillance in China. Graphic Abstract